2015
DOI: 10.1177/2158244015615919
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotically Induced Out-of-Body Experience

Abstract: The possibility to induce real out-of-body experiences (OBEs) using hypnotic inductions, with the opportunity to interview participants during their experience, permits to investigate in depth the characteristics of different aspects of this particular state of consciousness from a first-person point of view. In this article, six selected participants report the description of another "body" we named "subtle body," identified as an intermediate entity between the physical body (Pb) and their "Self" or "I-ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…As pointed out in the paper for the previous study (Tressoldi, 2015), during the participants' training, the hypnotist noticed that some of them perceived a type of secondary body, an intermediate between the physical body (Pb) and a form of disembodied personal selfhood (DPS). The participants described this body, which was simply named "subtle body" (Sb) to differ it from the Pb and from the center of consciousness or first-person perspective we named "psychic body" (Ψb) plus the interaction among them.…”
Section: Hypnobe Groupmentioning
confidence: 80%
See 2 more Smart Citations
“…As pointed out in the paper for the previous study (Tressoldi, 2015), during the participants' training, the hypnotist noticed that some of them perceived a type of secondary body, an intermediate between the physical body (Pb) and a form of disembodied personal selfhood (DPS). The participants described this body, which was simply named "subtle body" (Sb) to differ it from the Pb and from the center of consciousness or first-person perspective we named "psychic body" (Ψb) plus the interaction among them.…”
Section: Hypnobe Groupmentioning
confidence: 80%
“…The ten participants who were induced into an OBE by using hypnotic suggestion were selected based upon a high degree of hypnotisability and a willingness to experience this particular state of consciousness, as well as previous experience with the research team. More details about the procedure for OBE induction are reported in Tressoldi et al, (2015); Tressoldi et al, ( 2014). A complete description of this procedure is presented by Pederzoli and Tressoldi( 2018).…”
Section: The Hypnotic Obe (Hypnobe) Group Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Cardeña & Alvarado, 2014). Two previous pilot studies (Pederzoli et al, 2016;Tressoldi et al, 2014Tressoldi et al, , 2015 have shown the possibility of inducing OBEs by specific hypnotic suggestions, thereby making it possible to prospectively explore their phenomenological features and their electroencephalographic (EEG) correlates under controlled conditions. A recent phenomenological comparison among OBEs experienced within NDEs, spontaneous nontraumatic OBEs and those induced by hypnosis (H-OBE) (De Foe, Al Khafaji, Pederzoli, Prati, & Tressoldi, 2017) has shown several similarities; they included an increased awareness associated with positive emotions (e.g., "It was as if suddenly I knew everything that was being communicated.…”
mentioning
confidence: 99%
“…(Cardeña & Alvarado, 2014). Two previous pilot studies (Pederzoli et al, 2016;Tressoldi et al, 2014Tressoldi et al, , 2015 have shown the possibility of inducing OBEs by specific hypnotic suggestions, thereby making it possible to prospectively explore their phenomenological features and their electroencephalographic (EEG) correlates under controlled conditions.…”
mentioning
confidence: 99%